Subband transforms for CDMA systems - Lee, Weng Chye. (2008)
This thesis presents a new technique to enhance interference immunity of a spread spectrum system. Interference in the received signal is suppressed using this technique before the despreading operation takes place. Instead of the conventional Fourier transform, wavelet transform is employed in this technique. Wavelet transform provides valuable time information about the received signal. Therefore making it easy for the exciser to detect non-stationary and impulsive interference.